Histologické nálezy u nádorů ledvin - Hora, M; Ouda, Z; Schejbalová, E; Chudácek, Z; Mukensnabl, P (Rozhledy v chirurgii, 1997)
The authors present a group of 304 adult patients (with the exception of one child with a Wilms tumour) from 1988-95 with the diagnosis of a primary renal tumour treated by surgery and subsequently subjected to histological examination. The tumours were in 83.9% clear renal cell tumours (Grawitz carcinoma), 4.3% were papillary carcinomas, 3.3% renal cortical adenomas, 3.9% oncocytomas and 2.0% non-differentiated carcinomas, 0.7% angiomyolipomas, 0.7% chromophobe cell renal carcinomas, 0.7% secondaries (carcinoma of the breast and testis), 0.7% multilocular cysts, one case each (0.3%) Wilms tumour, malignant lymphoma, necrotic histologically not classifiable tumour. The authors give a more detailed account of multilocular cystic RCC (which accounts for 5.9% Grawitz tumours), papillary tumours, chromophobe cell renal carcinoma, oncoytoma and angiomyolipoma. The authors correlate briefly the histological findings with preoperative graphic examinations. They are very sceptical as regards assessment of the histological type of tumour from preoperative graphic examination (with the exception of angiomyolipoma). Finally the authors suggest classification of renal expansions from the urologists aspect-in the first place from preoperative graphic examinations for non-neoplastic lesions (in particular cysts and hypertrophy of the columna Bertini), parenchymatous tumours and tumours of the renal pelvis and secondly (mainly in parenchymatous tumours) histological classification is taken into account.
Keywords: dospělí; Humans; Adult; lidé; Kidney Neoplasms; dítě; nádory ledvin; Child